Comparison of Antibacterial Activity and Physicochemical Characteristics of Vco (Virgin Coconut Oil) With Different Manufacturing Methods - Hadi, Hana Safitri Putri; Sarkono; Kusuma, A.A. Ngurah Nara; Kholidi, Muh. Azhar (Yayasan Siti Widhatul Faeha, 2026)
Cocos nucifera is an important plantation commodity in Indonesia with high economic value and considerable potential for the development of value-added products, including Virgin Coconut Oil. This study aimed to compare the physicochemical characteristics and antibacterial activity of VCO produced using heating, fermentation, and enzymatic methods. The research was conducted experimentally from June to August 2024 at the Advanced Biology Laboratory, Faculty of Mathematics and Natural Sciences, University of Mataram. VCO samples were evaluated through organoleptic tests and physicochemical analyses, including yield, moisture content, peroxide value, and free fatty acid content. Antibacterial activity was tested against Staphylococcus aureus and Escherichia coli using the disk diffusion method. The results showed that all VCO samples generally met Indonesian National Standard quality requirements, except for free fatty acid content in some treatments. The fermentation method produced the highest yield (31.88%), while the heating method resulted in the best overall quality, characterized by 0% moisture content, 0 mg Eq/kg peroxide value, and the highest organoleptic acceptance. All VCO samples exhibited antibacterial activity, although the inhibition zones were categorized as weak. The findings indicate that the heating method is the most suitable for producing high-quality VCO with antibacterial potential.